ANALISIS PERBANDINGAN KINERJA PORTOFOLIO BERDASARKAN PRICE EARNING RATIO (PER)DI BURSA EFEK INDONESIA - Komang Tri Wahyuni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Research of stock portfolio performance based on Price Earning Ratio (PER) is still a debate. The purpose of this research is to analyze the performance of stock portfolio based on PER at Indonesian Stock Exchange during period 2014 - 2016, in addition of these reaserch is to test the comparison of stock portfolio performance between high PER and low PER. Performance stock portfolio based on PER is measured by Risk Adjusted Return (index of Sharpe, Treynor and Jensen), and comparison stock portfolio performance between high PER and low PER is tested by using statistic analysis independent sample t-test. The result of these research are low PER is outperform than high PER measured by index Sharpe and index Treynor, but high PER outperform if measured by index Jensen during periode 2014 – 2016 at Indonesia Stock Exchange and t-test analysis between high PER and low PER is founding that stock portfolio high PER and low PER measured by index Treynor and index Jensen is difference significantly, but measured by index Sharpe is not difference significantly.